Coping strategies and caregiver's anxiety in pediatric oncohematology - Kohlsdorf,Marina (2011)
The main goal of this paper was to investigate associations between sociodemographic data, patient's clinical condition, indicators of anxiety, and coping strategies adopted by caregivers during leukemia diagnosis in order to indicate which factors may influence anxiety and the adopted coping strategies. In this study, 44 caregivers were enrolled and submitted to the Ways of Coping Scale (Brazilian Version - EMEP), the Beck Anxiety Inventory (BAI), and a sociodemographic questionnaire. Results show associations among different coping categories, caregiver's age, education, and the presence of a spouse, as well as correlations related to anxiety, subject's gender, and the children's age. There was relevant association between anxiety and emotion-focused coping, suggesting the importance of interventions during the early stages of the treatment.